Christians and the common good : how faith intersects with public life - Gutenson, Charles E. (Grand Rapids, Mich. : Brazos Press, 2011)
"Christians across the spectrum have soured on religious involvement in politics, tempted either to withdraw or to secularize their public engagement. Yet the kingdom of God is clearly concerned with justice and communal well-being. How can Christians be active in public life without getting mired down in political polarization and controversy? For too long, the question of faith in public life has centered on what the Bible says about government. Charles Gutenson, a theologian respected by both evangelical and mainline Christians, argues that we should ask how God intends for us to live together before considering particular public policies and governmental institutions. By concentrating on the nature of God, we can move past presuppositions regarding the role of government and form a reasonable framework for engaging in healthy discussions about how best to serve the common good. This lucidly written book will appeal to readers interested in ethics, theology, and politics and includes a foreword by bestselling author Jim Wallis" -- Publisher description.
Faith and politics -- Reading Scripture -- The God of Abraham, Isaac, Jacob, and Jesus -- Biblical vignettes -- Human governance and the kingdom agenda -- Public policy and the kingdom agenda.
Includes bibliographical references (p. 173-176) and index.
Keywords: Common good -- Religious aspects -- Christianity; Common good -- Biblical teaching